Analisis Yuridis terhadap Peran TNI dalam Perlindungan dan Pengelolaan Lingkungan Hidup Berdasarkan Hukum Positif di Indonesia: A Legal Analysis of the Role of the Indonesian National Armed Forces in Environmental Protection and Management Based on Positive Law in Indonesia - Aan Tirta Gandana; Agus Hendrayana; Dainsyah; Dian Amalia Dewi; Yudha Permana Sidiq; Edy Santoso; Nugraha Pranadita (SIYASI: Jurnal Trias Politica, 2025)
Environmental crimes in Indonesia are cross-sectoral and long-term, often exceeding the capacity of civilian enforcement and thus requiring limited support from the armed forces (TNI) under Military Operations Other Than War (OMSP). This article aims to: (1) map the TNI’s role in environmental law enforcement as a proportional supporting actor; (2) assess regulatory coherence and jurisdictional limits under Law No. 34/2004 (TNI) and Law No. 32/2009 (Environmental Protection and Management); and (3) propose an accountable evaluation matrix for TNI involvement. We employ a normative juridical method with statute, conceptual, and case approaches (Citarum Harum and the maritime domain), combined with policy analysis and document review (laws, presidential regulations, MoUs, strategic plans) triangulated with scholarly literature. Findings indicate that judicial authority remains with environmental civil investigators/police and prosecutors, while the TNI contributes to area/scene security, situational stabilization, mobilization, and logistics—subject to prompt handover, preserved chain of custody, and clear inter-agency SOPs. In the maritime domain, effectiveness hinges on interoperability and deconfliction; on land (forestry/mining), support is effective when paired with strengthened environmental forensics and investigator capacity. The novelty lies in a four-dimensional evaluation matrix (legal mandate & jurisdictional limits; operational roles & interoperability; forensic evidentiary quality; governance accountability & legitimacy) accompanied by guardrails to prevent overreach. Policy implications highlight the need for detailed secondary regulations on assistance tasks, collaborative performance indicators, and data transparency so that TNI involvement acts as a catalyst rather than a substitute for environmental law supremacy.